Hedging their bets? The case for a European pillar in NATO. Issue 4 (1st October 2020) - Ringsmose, Jens; Webber, Mark
ABSTRACT: President Donald Trump has adopted a critical position on NATO, raising concerns of an American abandonment of its obligations to Europe's defence. The severity of Trump's position is unusual, but some of his concerns are of long-standing and likely to be voiced in some form by his successor in the White House. American criticism and equivocation has led the European allies to engage in various forms of hedging. Some of these strategies are designed to keep the US attached to NATO; others bypass the alliance – cultivating either bilateral links to the US or a strengthening of EU defence cooperation. Hedging, whatever its form, is potentially damaging to alliance effectiveness and cohesion. In that light, NATO's interests are better served by a strategy which builds upon the NATO-EU relationship and which advertises the benefits of European effort within NATO itself. To that end, we argue in favour of a reformulation of an old but much misunderstood idea – that of NATO's "European pillar." Here, existing contributions to European defence provided by the allies through NATO are crucial. Such an arrangement need not, therefore, entail any elaborate institutional engineering, but it does require political and strategic clarity.